Analysis of Medical Record Document Filling Completeness of Outpatient at Nala Husada Dental Hospital - Caecilia Indarti; Lita Agustia (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Medical records (RM) as patient health information recorded assessment results, plans and implementation of care, treatment, integrated patient progress, as well as a summary of discharge for inpatients made by PPA. The results of medical record documents tracing at the Nala Husada dental hospital found that the RM was incomplete. This study aims to analyze the completeness of medical records filling that does not align with the accreditation standard of medical records management and health information (MRMIK). This study identified causal factors as a follow-up to implementing patient medical record management. It was conducted quantitatively with a descriptive observational approach. Data was obtained through observation, interviews, and documentation at the medical record unit during July 2022. The data was then processed and analyzed. Based on the analysis of the completeness of the 80 file documents, 86.25% were found to be complete, and 13.75% were incomplete. Incomplete medical record documents with good records were 17.4%, 16% important reports/records, 12.5% author authentication, and 8% patient identity. Factors causing incomplete filling of medical record documents with the management element approach included human error (lack of understanding and discipline, limited number of staff, training), Material and Machine (limited equipment, various documents, unspecific evaluation monitoring review), and method (incomplete regulatory studies), monitoring and evaluation are not continuous), and money (not included in the program budget plan). Recommendations to improve the completeness of medical record filling were training, sanctions, and rewards, regulation review, procedures for filling as per PPA requirements, and standardization of medical record forms.